Elevated arsenic in deeper groundwater of the western Bengal basin, India: Extent and controls from regional to local scale - Mukherjee, Abhijit; Fryar, A.; Scanlon, B.; Bhattacharya, P.; Bhattacharya, A. (Pergamon, 2011)
The deeper groundwater (depending on definition) of the Bengal basin (Ganges-Brahmaputra delta) has long been considered as an alternate, safe drinking-water source in areas with As-enrichment in near-surface groundwater. The present study provides the first collective discussion on extent and controls of elevated As in deeper groundwater of a regional study area in the western part of the Bengal basin. Deeper groundwater is defined here as non-brackish, potable (Cl - =250mg/L) groundwater available at the maximum accessed depth (~80-300m). The extent of elevated As in deeper groundwater in the study area seems to be largely controlled by the aquifer-aquitard framework. Arsenic-enriched deeper groundwater is mostly encountered north of 22.75°N latitude, where an unconfined to semi-confined aquifer consisting of Holocene- to early Neogene-age gray sand dominates the hydrostratigraphy to 300m depth below land surface. Aquifer sediments are not abnormally enriched in As at any depth, but sediment and water chemistry are conducive to As mobilization in both shallow and deeper parts of the aquifer(s). The biogeochemical triggers are influenced by complex redox disequilibria. Results of numerical modeling and profiles of environmental tracers at a local-scale study site suggest that deeper groundwater abstraction can draw As-enriched water to 150m depth within a few decades, synchronous with the advent of wide-scale irrigational pumping in West Bengal (India). © 2011 Elsevier Ltd.